The cascade of care for latent tuberculosis infection in congregate settings: A national cohort analysis, Korea, 2017–2018 - Jinsoo Min; Hyung Woo Kim; Helen R. Stagg; Molebogeng X. Rangaka; Molebogeng X. Rangaka; Marc Lipman; Marc Lipman; Marc Lipman; Ibrahim Abubakar; Ibrahim Abubakar; Yunhee Lee; Jun-Pyo Myong; et al. (Frontiers in Medicine, 2022)
BackgroundIn 2017, Korea implemented a nationwide project to screen and treat latent tuberculosis infection (LTBI) in high-risk for transmission public congregate settings. We aimed to assess programme success using a cascade of care framework.Materials and methodsWe undertook a cohort study of people from three congregate settings screened between March 2017 and December 2018: (1) first-grade high school students, (2) employees of educational institutions, (3) employees of social welfare facilities. We report percentages of participants with LTBI completing each step in the cascade of care model. Poisson regression models were used to determine factors associated with not visiting clinics, not initiating treatment, and not completing treatment.ResultsAmong the 96,439 participants who had a positive interferon-gamma release assay result, the percentage visiting clinics for further assessment, to initiate treatment, and who then completed treatment were 50.7, 34.7, and 28.9%, respectively. Compared to those aged 20–34 years, individuals aged < 20 years and aged ≥ 65 years were less likely to visit clinics, though more likely to complete treatment once initiated. Using public health centres rather than private hospitals was associated with people “not initiating treatment” (adjusted risk ratio [aRR], 3.72; 95% confidence interval [CI], 3.95–3.86). Nine-month isoniazid monotherapy therapy was associated with “not completing treatment,” compared to 3-month isoniazid and rifampin therapy (aRR, 1.28; 95% CI, 1.16–1.41).ConclusionAmong participants with LTBI from three congregate settings, less than one third completed treatment. Age, treatment centre, and initial regimen were important determinants of losses to care through the cascade.